Pelatihan Pembuatan Media Pembelajaran Bangun Datar Berbasis Ecopreneurship - Suci Prihatiningtyas; Fahmi Fachrurrozie; Muhamad Khoirur Roziqin; Yunita Wulandari; Dinda Fajru Lil Ummah; Norma Linda Yanti (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2024)
Learning cannot be separated from learning media which functions to facilitate students' learning activities. Training on making learning media. Flat buildings become key chains in the context of P5 (Pancasila Student Profile Strengthening Project) Merdeka Belajar is an innovative way to integrate education with ecopreneurship principles. This training aims to enable MI Asy-Syafiiyah students to memorize flat shapes through ecopreneurship-based learning media, and so that MI Asy-Syafiiyah students can have an entrepreneurial spirit from an early age. The approach method for implementing community service activities includes demonstration and workshop (training) methods. For data collection methods, interviews were used with class teachers and school principals. This training was attended by 30 MI Asy-Syafiiyah students. The results of the training socialization which was carried out in 3 stages, namely the planning stage, implementation stage and evaluation stage, received a good response from the students and teachers of MI Asy-Syafiiyah, marked by an increase in students' understanding of spatial construction and the spirit of ecopreneurship being embedded in the students.